FAKTOR MOTIVASI KERJA YANG MEMPENGARUHI PRODUKTIVITAS PEGAWAI SEKTOR PUBLIK DI INDONESIA - Rhama Agung Sanjaya; Habbi Firlana; Mas Budi Priyatno (POLITEKNIK LP3I JAKARTA, 2025)
This study systematically reviews literature to analyze the factors influencing work motivation and their impact on the productivity of public sector employees in Indonesia. By examining intrinsic and extrinsic motivational drivers, organizational culture, and social-psychological factors, the review highlights how these elements collectively shape employee performance. Intrinsic motivation, including personal satisfaction and self-development, fosters commitment and creativity, while extrinsic motivation through rewards and recognition reinforces work enthusiasm. Organizational factors such as a supportive culture, fairness, and effective communication further enhance motivation and productivity. Social aspects, including interpersonal relationships and social recognition, contribute to a conducive work environment. However, the study also identifies internal and external barriers—such as ineffective leadership, bureaucratic constraints, limited resources, and policy dynamics—that hinder motivation and productivity improvements. The research is limited by its reliance on secondary data from literature, lacking empirical validation through primary data collection. Future studies are recommended to employ mixed-method approaches and incorporate additional variables to provide a more comprehensive understanding of productivity determinants in the public sector. Overall, this review underscores the critical role of multifaceted motivational factors in enhancing public sector employee productivity and offers insights for policymakers and managers aiming to optimize workforce performance in Indonesia.